The mediating role of self-efficacy in the relationship between emotional intelligence and organizational commitment - Hameli, Kujtim (2022)
Purpose – This study examines the relationship between emotional intelligence, self-efficacy and organizational commitment, focusing on the mediating role of self-efficacy in the relationship between emotional intelligence and organizational commitment. Design/methodology/approach – The authors used an online survey to collect data for this purpose. The sample consisted of 145 employees of different organizations in Kosovo. To test the hypothetical model, a mediation analysis was conducted using PROCESS Model Type 4. Findings – The results show that emotional intelligence is positively related to self-efficacy and that self-efficacy is positively related to organizational commitment. Furthermore, the results of themediation analysis confirmthat the relationship between emotional intelligence and organizational commitment is mediated by self-efficacy. Research limitations/implications – For future research, the authors recommend using the sub-dimensions of the above variables to test thismodel, andmultiplemodels could be formulated.At the same time, the survey can be applied to managers to examine their emotional intelligence and to determine whether emotional intelligence influences their organizational commitment through self-efficacy. Consistent with the findings of this study, managers and executives in organizations should consider the emotional intelligence of their employees and that the employees with higher emotional intelligence have higher self-efficacy and can perform better. Originality/value – This study extends the current literature in organizational behavior and provides a comprehensive understanding of the relationship between emotional intelligence, self-efficacy and organizational commitment. This study was also conducted in a developing country context, which can always lead to different results than studies conducted in developed countries.